Application of Household Accounting in Improving Islamic Life (Survey of Housewives on Jl Puro) - Rasmi Nur Anggraeni; Jurana Jurana; Dasa Febrianti; Sri Haryani; Marwana Marwana; Cahyaning Raheni (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
Economic problems are the most phenomenal problems in the many breakdowns of a household. For this reason, this study aims to review the role of accounting in the household and find out how to apply Islamic household financial management. This type of research is qualitative research. This study only uses informants, namely housewives who come from families with Muslim backgrounds and have applied simple accounting in managing their household finances, such as doing financial records every month. The analysis used in this study is a qualitative method with a terminological approach so that all answers from informants to questions given by researchers will be analyzed and studied in detail. This study shows that homemakers have implemented most of the components in Islamic household financial management, namely saving for the pilgrimage, alms, and zakat to get a reward from Allah SWT.